Screen time, mute, mixed messages, and panic: An international auto-ethnographic study of knowledge workers during a pandemic - Mark Finney; Jacqueline O’Reilly; Claire Wallace (Qualitative Research in Medicine & Healthcare)
The coronavirus pandemic provoked worldwide changes to the workplace, leading to rapid changes in lifestyles and working conditions. While organizations and governments struggled to develop regulations and policies, individuals were forced to find ways to manage work and life. During the pandemic and quarantine, a group of knowledge workers from around the world convened virtually and agreed to use qualitative autoethnographic methods to study how the quarantine disrupted their conventional patterns of work and care. In this article, we apply two communication perspectives—uncertainty reduction theory and resilience— to participant diaries to understand how participants represent internal and external stressors, the efforts diarists employed to overcome those stressors, and their varying success in doing so. Post-hoc application of these communication concepts suggests that the diarists, though privileged in some ways, were not exempt from the social, professional, and emotional consequences of the pandemic and that their efforts to enact resilience were unevenly successful, especially in relation to their use of communications technology. Diarists reported struggling with uncertainty at numerous levels and that uncertainty contributed to individual emotional and cultural distress. Disruptions to work, home, and communities significantly affected wellbeing and ability to cope with challenges. Added to this were the complex and competing roles that diarists felt as they struggled to work from home, parent, and remain engaged.